Fiqh Budaya dalam Perspektif Tarian Tayub Pada Tradisi Sedekah Bumi - Maskur maskur (Universitas Wahid Hasyim Semarang, 2021)
Tayub dance is held as one of the things that must be held every the implementation of the earth alm tradition. Tayub dance in the tradition of alms in Plaosan Village, Cluwak district, regency is an interesting center to be studied, especially from the perspektif of cultural fiqh. The focus of research in this study is related to the study of cultural fiqh which views the tayub dance ritual in the tradition of almsgiving in the village of Plaosan, Cluwak district, Pati regency. The reseach metod in this research is qualitative which describes in detail the reseach focus. The results showes that tayub dance as a mandatory ritual of the earth alms tradition is an activity carried out as an expression of joy and a form of gratitude to God Almighty. Based on the study of cultural fiqh in tayub dance. Basically it sees an important part that the tradition of dancing is not somethings that is prohibited bs Islam as long as it does not cause deterioration and mislead the community. Thus it permissible todo so because it does not contradict religious law.